Role of quinolones and quinoxaline derivatives in the advancement of treatment of tuberculosis - Asif, Mohammad (International Journal of Scientific World, 2015)
The need of new chemotherapeutic drugs to improve tuberculosis control and treatment particularly against multidrug-resistant (MDR) and extensively drug resistant (XDR) strains of Mycobacterium. The atitubercular drugs are used in current chemotherapy have different chemical moieties. In this review, we provide an overview of the quinolone drugs as an antitubercular drug. Generally quinolone drugs are mainly used against many gram-positive and gram-negative bacterial infections including resistance strains also. Various quinolones are being used to control and treatment of tubercular infections including MDR, XDR and atypical Mycobacterium strains. Fluoroquinolones are an important quinolones, especially for strains that are resistant to first-line agents.